Influence of marital status, parenthood and housework on women’s attitude towards paid employment in Calabar, Nigeria - Etuk, Grace Reuben; Etuk, Reuben Ufot; Iyam, Ukam Ilem (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
For economic and other social and psychological reasons, most developing countries are currently witnessing a massive influx of women into workforce. One sure way of empowering women and reducing gender inequality in today’s fast changing world, especially in a developing society like Nigeria, is by getting more women actively engaged in economic activities to improve their financial status. Although most of the women are found in the informal and private sectors, where their contributions to society may not be adequately felt, a recognizable proportion is still found in the formal sector where they function as actors in development and in turn receive regular salaries. In view of their increasing involvement in paid employment, this study investigates the extent of influence such familial factors as marital status, parenthood and housework have on the attitudinal disposition of female Public Servants towards paid employment in Calabar Metropolis, Nigeria. Results reveal that for both married and single women in the study, housework and child care are both very stressful and combining both tasks with paid employment is even more demanding. Results further showed that the highly demanding task of having to combine childcare and housework with paid employment results in incidences of negative attitudinal trends among subjects. The implications of this to sustainable development are considered and possible solutions to solving this dilemma of women are also suggested.